(3eMGSHI GdLhOI (B:s (3eONd JMdjdj (B/s - (3GdSjO, fGXe MSf YHOs ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2009)
(3eONd JYQjaj ddLhOI(B- (3GdLPhQ GdadSajI hhLgGJ GdfXQ Mhd GdLhOI(B- (3CgejI GdLhOI(B- (3eaghe JcGdja GdLhOI hechfGJgG(B- (3eONd JYQjaj dbjGS JcGdja GdLhOI(B- (3JMdjd JcGdja GdLhOI(B- (3fJGFL bjGS hJMdjd JcGdja GdLhOI(B- (3GdGOGA GdeGdj(B- (3GdJhLgGJ GdMOjKI dbjGS GdCOGA(B- (3ebGjjS GdGOGA GdeGdj(B- (3fJGFL bjGS hJMdjd JcGdja GdLhOI hCKQgG aj JMSjf GdCOGA GdeGdj(B- (3OQGSI MGdIs
(3GdedGMb U(B213(3; GdeQGLY U(B217s
Keywords: (3GdEjRhs; (3GdeMGSHIs; (3LhOI GdEfJGLs; (3VHW GdLhOIs; (3eQGbHI GdEfJGLs